2016
DOI: 10.1007/s13197-016-2422-6
|View full text |Cite
|
Sign up to set email alerts
|

Chickpeas suppress postprandial blood glucose concentration, and appetite and reduce energy intake at the next meal

Abstract: The current study was designed to explore the beneficial properties of chickpeas consumption on suppressing appetite, excessive blood glucose excursions, and energy intake (EI) from a subsequent meal. Two caloric preloaded foods, chickpeas, and white bread were compared to water control, fed to healthy female subjects at equal energy density, volume, and available carbohydrate content in two experiments spanning over 60 and 120 min. Blood glucose was measured by a portable glucometer and satiety by using a vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Similarly, the use of legumes in food formulation is assuming greater importance and has attracted the attention of food processors, marketers, and consumers (Boye et al., 2010; El-Bar et al., 2017; Nasir and Sidhu, 2013). Legumes are rich in both insoluble and soluble dietary fiber, especially resistant starch, which is digested relatively at a much lower rate than that of cereal starch, it can be utilized for attenuating the abnormal sugar spikes in blood after consuming such legume–cereal based composite flour bread and other food products (Wong et al., 2009; Zafar et al., 2015; Zafar and Kabir, 2017). Grain legume seeds, however, are reported to accumulate significant amounts of various glycoproteins (lectins, protease inhibitors) and other compounds (phenolics, saponins, alkaloids) that also affect their nutritional and functional properties (Campos-Vega et al., 2010; Harada et al., 2010; Pandey et al., 2006; Rachwa-Rosiak et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the use of legumes in food formulation is assuming greater importance and has attracted the attention of food processors, marketers, and consumers (Boye et al., 2010; El-Bar et al., 2017; Nasir and Sidhu, 2013). Legumes are rich in both insoluble and soluble dietary fiber, especially resistant starch, which is digested relatively at a much lower rate than that of cereal starch, it can be utilized for attenuating the abnormal sugar spikes in blood after consuming such legume–cereal based composite flour bread and other food products (Wong et al., 2009; Zafar et al., 2015; Zafar and Kabir, 2017). Grain legume seeds, however, are reported to accumulate significant amounts of various glycoproteins (lectins, protease inhibitors) and other compounds (phenolics, saponins, alkaloids) that also affect their nutritional and functional properties (Campos-Vega et al., 2010; Harada et al., 2010; Pandey et al., 2006; Rachwa-Rosiak et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Canned chickpea grains were found to suppress satiety and energy intake from a test meal consumed 120 min after the preload meal [ 42 ]. However, chickpea as flour was not found to impact satiety.…”
Section: Resultsmentioning
confidence: 99%
“…It is also particularly high in fiber. Studies have shown that people with type 1 diabetes who consume high-fiber diets have lower blood glucose levels, and for people with type 2 diabetes, higher fiber intake can improve and stabilize blood sugar, lipids, and insulin levels [44,45]. It has a low glycemic index, preventing blood sugar levels from rising too rapidly after a meal, and this makes it an especially good choice for people suffering from diabetes, insulin resistance, or hypoglycemia.…”
Section: Chickpea Has Diversified Food Nutrition Feed Uses and Health Benefitsmentioning
confidence: 99%